ANALISIS PENGUNGKAPAN SOSIAL PADA LAPORAN TAHUNAN - Henny Henny; Murtanto Murtanto (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2001)
The aim of this study is to provide a view of social disclosure practices in company annual reports and analyses the different on these practices between high profile and low profile companies. A sample of 58 firms listed on Jakarta Stock Exchange is taken using the proportionate stratified random sampling method. Content analysis method is used to examine the 1999 annual reports with regard to the content, location and type of disclosure made by the sample, then to determined whether there is a significant difference on social disclosures made between high profile and low profile companies, a statistical analysis is done using the Z test. Fifty-five items are included in the social disclosures list, which are classified into 6 areas: customer and product, environment and energy, business alliances, stockholders, community involvement, and human resources.The results of this study shows that social disclosures in Indonesia were still relatively low, only 41,32% of the items included in the list was disclosed by the firms. The majority of social responsibility disclosures were in the areas of human resources. Most of the disclosures were located in the management report and notes on financial statement Types of the disclosures were mixed in narrative qualitative, quantitative non monetary, and quantitative monetary. The statistical test proved that there was a significant difference on social disclosures made by high profile and low profile companies. The disclosures made by high profile companies were higher than low profile companies. The results of partial testing on these practices in each area show that a significant difference between the two types of companies exists only in three areas: environment and energy, business alliances, and human resources areas. In the environment and energy and the human resources areas, social disclosures made by high profile companies were higher than low profile ones.